Group treatment manual for persistent depression : cognitive behavioral analysis system of psychotherapy (CBASP) : therapist's guide /: cognitive behavioral analysis system of psychotherapy (CBASP) : therapist's guide. (2016) - Sayegh, Liliane; Penberthy, J. Kim
No abstract available